Kebijakan Kampus Merdeka Mendorong Mahasiswa Berdaya Saing Global? - Ahmad Jahroni; Eli Fitriyani; Muhamad Faisal Hafiz (Journal of Information Systems and Management (JISMA), 2025)
The purpose of this study is to find out the independent campus policy through merdeka Belajar. This study report uses a descriptive qualitative method by observing notes because the data source is obtained by listening to the oral narration from the KEMENDIKBUD RI Youtube channel entitled "Merdeka Belajar Episode 2 Kampus Merdeka" presented by Nadiem Anwar Makarim. The results of this study explain that the independent campus policy is to encourage students to master various sciences that are in accordance with their fields of expertise so that they are ready to compete in the global world. This policy provides opportunities for students to choose the courses they will take based on their own desires. Each activity chosen by students must be guided by a lecturer determined by the campus. The list of activities that can be taken by students can be selected from programs determined by the government and or programs approved by their rektor.